Fabrication of Continuous Fire Wire Detection Sensor usingNegative Temperature Coefficient Material - Singla, M.L.; Pandey, V.S. (Defence Science Journal, 2007)
Manganese-based spinel semiconducting ceramic was mixed with lanthanum oxide powderand the mixture was characterised for the reproducible negative temperature coefficient (NTC)of resistance behaviour. The same mixture was used for the fabrication of 15 m long continuousthermal detector. The addition of La2O3 leads to decrease in thermistor constant and activationenergy values, thus giving freedom to fabricate thermal sensors for various temperatureapplications. A 3 m long continuous thermal detector for application in the temperature range275 - 350 oC was fabricated and later coupled to form a continuous unit of 15 m length.